As saídas singulares de professoras de língua inglesa frente à impossibilidade de educar - Caroline Martins dos Santos (2021)
The work presented here falls within the area of Applied Linguistics, in the field of teacher training, and reaches the area of Psychoanalysis as a theoretical support for the qualitative approach of clinical guidance. The research starts from the Lacanian studies of the four discourses to address the issue of the impossibility of educating. According to Freud (1937), education would be one of the three impossible functions, since it cannot be done effectively, together with the act of governing and analyzing. Considering this, I question how practicing teachers deal with this impossibility in their praxis and, at the same time, distance themselves from impotence, a possible path for many of these professionals. We start from the assumption that there is no single way to educate in the face of impossibility, but each teacher invents unique ways to do so in their context. Once the singularity is considered as a means of analyzing these teachers, we propose to analyze the interviews of English teachers from regular schools in Belo Horizonte in order to understand what is unique about their practices that allows them to place themselves in the school environment in a vivid way. In addition to the collection of the corpus through recorded interviews, there is also the analysis of the researcher's clinical diary, used during the interviews and conversations that take place during the Pedagogical Rounds in the ConCol / UFMG ongoing teachers training project. In addition to seeking to understand the uniqueness of the teachers interviewed, we intend to take a close look at the choice of English language by these teachers who invest their desire in school, besides the role of continuing education in the process of subjectivizing their teaching activities. During the analysis process of the participants 'statements, some rich concepts for research are considered, such as the concept of teaching style, the result of the investigation of the teachers' singularities, as well as unusual paths that research in Psychoanalysis leads us to take. In view of the objectives proposed for the research and a careful look at the commitment to comply with the proposed methodology, we get, among others, at some main answers, considering also what is unique to each one of the teachers: 1) both teachers, based on their experiences and in the desire to educate, they invent ways out of deadlocks in the classroom routine that tells us of a style built over time and consolidated through their subjective bets; 2) there is something about the desire to educate that goes beyond the context of the classroom, but it is associated with the English language, not so much as an object of teaching, but as an object of desire to enjoy the language as do other people in their lives and, therefore, finally, 3) the practice of the participating teachers is also permeated by a malaise arising from a jouissance that causes the body, each in its own way, in our view, symptomatic teaching. Thus, we conclude that although both present singular solutions to the impossibility of educating and show a desire to live in school, there is a malaise associated with teaching, which may have different reasons that the research does not propose to discuss, since it would be from another type of investigation.